Effects of natural variation in snow depth on growth, flowering phenology and clonal structure of the evergreen dwarf shrub Empetrum hermaphroditum Hagerup - Bienau, Miriam Judith (2023)
Arctic and alpine ecosystems are characterized by a cold and relatively short growing season. Within these landscapes topography and prevailing wind directions shape heterogeneous snow distribution patterns. The heterogeneous snow distribution leads to habitats differing in snow depth during winter and snow melt timing in spring. The alpine tundra represents a mosaic of early-melting habitats on wind-exposed ridges with shallow snow cover, and late-melting habitats in wind-sheltered depressions with deep snow cover. Also in sub-arctic birch forest, birch stems act as snow traps, leading to accumulation of snow. Consequently, the various habitats are characterized by plant species and communities, which avoid and prefer snow cover, respectively. However, some species occupy a wide range of habitats and intraspecific differences in responses to variation in snow depth and duration can affect growth habit, phenology and reproduction. The response of plant species along natural gradients might be similar to temporal changes of environmental conditions. Thus, studies along environmental gradients, encompassing the range of climate change predictions, is more likely to give a realistic picture concerning extent of intraspecific phenotypic trait variation, which may determine the long-term adaptive potential of plant species to climate change. Arctic ecosystems face strong changes in snow conditions due to global warming by an increase in temperature, most pronounced in winter and spring, causing an earlier onset of snowmelt and an earlier start of the growing season. One such species with a broad habitat range is Empetrum hermaphroditum, a prominent evergreen dwarf shrub in several subarctic heath and mountain birch forest communities. The present study investigated growth, flowering phenology, reproduction and clonal structure of Empetrum hermaphroditum along a natural snow cover gradient in four study areas. The study areas are located along a latitudinal gradient (northern Sweden vs. central Norway), and at each ...